2018
DOI: 10.1080/22423982.2018.1508320
|View full text |Cite
|
Sign up to set email alerts
|

Childhood violence and mental health among indigenous Sami and non-Sami populations in Norway: a SAMINOR 2 questionnaire study

Abstract: The main objectives of this study were to investigate the association between childhood violence and psychological distress and post-traumatic stress symptoms (PTS) among Sami and non-Sami adults, and to explore a possible mediating effect of childhood violence on any ethnic differences in mental health. This study is part of a larger questionnaire survey on health and living conditions in Mid- and Northern Norway (SAMINOR 2) which included 2116 Sami and 8674 non-Sami participants. A positive association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 55 publications
3
19
0
10
Order By: Relevance
“…However, that study did not focus on the relationship between the victim and the abuser. Another study found an association between childhood abuse and mental health symptoms in adulthood (27). To our knowledge, there has not been any population-based study on IPV alone or IPV in combination with CV in Sami and non-Sami populations.…”
Section: Introductionmentioning
confidence: 90%
“…However, that study did not focus on the relationship between the victim and the abuser. Another study found an association between childhood abuse and mental health symptoms in adulthood (27). To our knowledge, there has not been any population-based study on IPV alone or IPV in combination with CV in Sami and non-Sami populations.…”
Section: Introductionmentioning
confidence: 90%
“…Mental health stigma is stronger, and the Sami are more frequently using traditional treatment forms [6]. Discrimination and childhood violence are more frequently reported with their negative effects upon mental distress [79]. A rigorous Norwegian assimilation policy, which included use of boarding schools where the Sami language was forbidden, took place particularly between 1860 and 1960.…”
Section: Introductionmentioning
confidence: 99%
“…In the SAMINOR 2 study, psychological distress was significantly higher in both Sami women (15.8 vs 13.0%) and men (11.4 vs 8.0%). Also posttraumatic stress symptoms were higher in the Sami: in women 16.2 versus 12.4 and 12.2 versus 9.1 in men [9]. However, these differences were small to negligible after adjustment for education, income, discrimination and resilience [8].…”
Section: Introductionmentioning
confidence: 99%
“…An abbreviated three-item version covering these domains were included in SAMINOR 2 (rated as 1-yes, but rarely, 2-sometimes and 3-often). This version has previously been used in the Nordic Study (Wijma, Schei, Swahnberg, Hilden, et al, 2003), in an European study on pregnant women (Schei et al, 2014), as well as in a previous sub-study of the SAMINOR 2 showing that childhood violence was strongly associated with posttraumatic stress in adulthood in both Sámi and non-Sámi populations (Eriksen et al, 2018). A principal component analysis of the three IES items yielded a single component with an eigenvalue 1 ( R -sq = 66.6%), thus supporting the creation of a single sum score.…”
Section: Methodsmentioning
confidence: 99%
“…Studies also report more frequent episodes of interpersonal violence during childhood, with women being particularly exposed (Eriksen et al, 2015). Those exposed, reported more mental distress and posttraumatic symptoms as adults (Eriksen et al, 2018), and more chronic pain (Eriksen et al, 2016). As such incidents may have occurred in school settings, as well as in homes, those with a boarding school history may have been at particular risk given the accumulation of ethnic- and school-related strains in these environments.…”
Section: Introductionmentioning
confidence: 99%